2019
DOI: 10.1029/2019jd030768
|View full text |Cite
|
Sign up to set email alerts
|

The Dependence of Shallow Cumulus Macrophysical Properties on Large‐Scale Meteorology as Observed in ASTER Imagery

Abstract: This study identifies meteorological variables that control the macrophysical properties of shallow cumulus cloud fields over the tropical ocean. We use 1,158 high‐resolution Advanced Spaceborn Thermal Emission and Reflection Radiometer (ASTER) images to derive properties of shallow cumuli, such as their size distribution, cloud top heights, fractal dimensions, and spatial organization, as well as cloud amount. The large‐scale meteorology is characterized by the lower‐tropospheric stability, subsidence rate, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
81
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(97 citation statements)
references
References 66 publications
14
81
2
Order By: Relevance
“…In the study of Nuijens and Stevens (), wind speed was found to influence the deepening of the boundary layer and cause deeper cloud layers. The effect of the wind on the boundary layer clouds is also confirmed by observations (Brueck et al ., ; Mieslinger et al ., ). Nuijens and Stevens () further emphasize that shallow cumuli get deeper with stronger winds, but not more numerous or more energetic, while the wind speed does not change the buoyancy flux in the mixed layer in equilibrium.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the study of Nuijens and Stevens (), wind speed was found to influence the deepening of the boundary layer and cause deeper cloud layers. The effect of the wind on the boundary layer clouds is also confirmed by observations (Brueck et al ., ; Mieslinger et al ., ). Nuijens and Stevens () further emphasize that shallow cumuli get deeper with stronger winds, but not more numerous or more energetic, while the wind speed does not change the buoyancy flux in the mixed layer in equilibrium.…”
Section: Discussionmentioning
confidence: 97%
“…Although there is a lack of observational studies on the large-scale control of the mass flux distribution, the cloud size distribution has been studied extensively. In a recent study by Mieslinger et al (2019), ASTER satellite imagery and the ERA-Interim reanalysis are used to test the controls of the large-scale meteorological conditions on the shallow cloud properties over the tropical oceans. Wind speed is recognized as a major factor controlling the cloud size distribution, among other cloud-based statistics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second, vertically pointing ATR cloud radar, allows a characterization of the aspect ratio of clouds, which may help infer the mesoscale circulations within the cloud field. These measurements, associated with new methods developed to estimate the cloud-base mass flux (Vogel et al, 2020), and to characterize the mesoscale cloud patterns from GOES-16, MODIS or ASTER satellite observations Mieslinger et al, 2019;Bony et al, 2020;Denby, 2020;Rasp et al, 2020), will make it possible to test cloud feedback mechanisms and advance understanding as to whether mesoscale cloud patterns influence the hypothesized feedback mechanisms.…”
Section: Testing Hypothesized Cloud-feedback Mechanismsmentioning
confidence: 99%
“…While perhaps not as important as organization (Minor et al, 2011) or cloud size (Jiang and Feingold, 2006), it is widely understood that aerosol concentrations act to suppress warm-rain production (Twomey, 1974;Albrecht, 1989) by increasing the cloud droplet concentration and reducing cloud droplet sizes (Squires, 1958). Albrecht (1989) found that increasing precipitation efficiency within a model is equivalent to decreasing the amount of cloud concentration nuclei (CCN), which reduces the mass concentration of cloud water within a cloudy layer.…”
Section: Introductionmentioning
confidence: 99%